Ability to Interpret Graphs in Reaction Rate Material Based on Mathematical Understanding and Learning Style of Class XI High School Students - Rezki*, Maulidia; Hasan, Muhammad; Evendi, Evendi; Akbar, Said Ali; Zaura, Bintang; Khwaengmek, Wipavadee (Jurnal Pendidikan Sains Indonesia, 2024)
One aspect of process science skills that learners need to have is the ability to interpret. The ability to interpret graphs in students is currently considered difficult and still belongs to the very low category. This study aims to analyze the relationship between mathematical understanding and the learning styles of students in terms of their ability to interpret graphs. This type of research is descriptive-quantitative. The research sample consisted of class XI students at SMA Negeri 4 Takengon, which amounted to 67 students. The research data was collected using learning style-type questionnaires, multiple-choice questions on linear program material, and reaction rate material. The ability to interpret the graphs of students at SMA Negeri 4 Takengon is on the "medium" criterion, while the students' mathematical understanding is on the "very high" criterion. Students with visual learning style types are more dominant and have an average score of mathematical understanding and the ability to interpret graphs higher than students with auditorial and kinesthetic learning styles. The result of the correlation coefficient r = 0.912 shows a significant positive relationship between mathematical understanding and the ability to interpret graphs with a "high" and unidirectional interpretation